(untitled) (Journal of Comparative & International Higher Education, 2024)
For almost four decades, Haiti has been engaged in the tenuous process of democratization, exacerbated by political, economic, social, climate, and more recently the COVID-19 crises. With each crisis, efforts are made to reimagine national development and revitalize the public sphere, with limited success. Yet, largely absent from these debates is the higher education sector. We argue that the neglect of higher education since Haiti’s transition from dictatorship to democracy is a result of the nation’s failure to articulate a clear vision for the sector. In this article, we ask: How has the failure to articulate a clear purpose for the higher education sector in Haiti exacerbated the country’s systemic crisis amid the COVID-19 pandemic? In order to answer this question, we provide a sociohistorical examination of the role of power and politics in Haitian higher education beginning in its founding in the 19th century culminating at the time of the pandemic. We explore how the absence of a strategic vision for higher education institutions in Haiti and ad-hoc neoliberal policies have impacted the professoriate and students while impeding the sector’s potential contributions to society in a time characterized by systemic and uninterrupted crises including the COVID-19 pandemic.